Cooking the Vietnamese way : revised and expanded to include new low-fat and vegetarian recipes - Nguyen Chi; Monroe Judy (Minneapolis : Lerner Publications, 2002)
An introduction to the cooking of Vietnam featuring such recipes as spring rolls, sweet and sour soup, and Vietnamese fried rice. Also includes information about the land, history, and holidays of this south-east Asian country.
Introduction: Land -- History -- Food -- Holidays and festivals -- Before you begin: Careful cook -- Cooking Utensils -- Cooking terms -- Special ingredients -- How to wrap spring rolls -- Healthy and low-fat cooking tips -- Vietnamese table: Vietnamese menu -- Vietnamese staples: Rice -- Rice noodles --Nuoc cham -- Carrot salad -- Soups and salads: Sweet and sour soup -- Shrimp salad -- Shredded chicken-cabbage salad -- Rice noodle salad -- Quick-cooked dishes: Fried rice -- Stir-fried beef with green beans -- Stir-fried cauliflower -- Spring rolls -- Grilled lemon grass beef -- Slow-cooked dishes: Braised chicken -- Sticky rice with corn and coconut -- Sweet potatoes with peanuts -- Steamed tofu -- Steamed fish -- Holiday and festival food: Asparagus soup -- Shrimp cakes -- New Year's caked -- Fresh fruit salad -- Index.
Includes index.
Keywords: Cookery Vietnamese -- Juvenile literature; Lowfat diet -- Recipes -- Juvenile literature; Vegetarian cookery -- Juvenile literature